Irruptions of crossbills Loxia spp. in northern Europe : patterns and correlations with seed production by key and non‐key conifers - Summers, Ron W.; Swallow, Ben; Fridman, Jonas; Hokkanen, Tatu; Newton, Ian; Buckland, Stephen T. (Wiley, 2024)
Irruptions by boreal seed-eating and frugivorous birds are assumed to be driven by the production of seeds and fruits, crops of which are highly variable between years. Using data from Sweden, we tested whether irruptions of Common Crossbills Loxia curvirostra were correlated with low Norway Spruce Picea abies seed production in the same year as the irruption and/or high seed production in the year prior to an irruption. Similar tests were made for Parrot Crossbill Loxia pytyopsittacus irruptions in relation to Scots Pine Pinus sylvestris seed production. In northern Europe, these conifers represent the key food species of the two crossbill species, respectively. Despite differing times that seeds take to mature and asynchronous seed production between the two conifer species, including a 3-year cycle for Norway Spruce, the two crossbill species often irrupted in the same year as one another. Analyses showed that irruptions into Britain and other parts of western Europe by both crossbill species were correlated with low seed production by Norway Spruce in Sweden. Low seed production by Scots Pine had a marginally non-significant additive effect on both crossbill species. In a second set of analyses, the best-fitting model was one in which low seed production by both conifers in a given year and high seed production in the previous year were each correlated with large numbers of irrupting Common and Parrot Crossbills. The models indicate that the incidental co-occurrence of low seed production of Norway Spruce and Scots Pine in a given year, after a year of high seed production, may result in an irruption. The seed production of Norway Spruce and Scots Pine in Sweden was correlated with production by the same species in Finland, indicating widespread synchrony of cropping across northern Europe.
Keywords: cone-crops; Falsterbo; Finland; seed production; Sweden